OP25 Benefits and Risks from Aspirin use in the Primary Prevention of Cardiovascular Disease and Cancer: A Systematic Review and Overview of Reviews of Randomised Trial Evidence. (10th September 2013) - Sutcliffe, P; Connock, M; Gurung, T; Freeman, K; Johnson, S; Kandala, N-B; Grove, A; Gurung, B; Morrow, S; Stranges, S
Abstract : Background: Although the overall benefits and risks are not yet clear, there is a policy push for use of aspirin to be used for primary prevention of CVD and cancer by healthy adults in the UK. We aimed to identify relevant randomised controlled trials (RCTs), systematic reviews and meta-analyses of RCTs to assess harms and benefits. Methods: Searches were performed in MEDLINE; EMBASE; Cochrane Database of Systematic Reviews; CENTRAL; DARE, NHS EED, HTA databases; Web of Science; UKCRN Portfolio Database and Clinical Trials.gov and were limited to publications since 2008. 2, 572 potentially relevant papers were identified. 27 met the inclusion criteria. Two reviewers independently extracted data. Results: Aspirin dose used and population inclusion criteria varied. Absolute effects of aspirin were small; for 5, 000 people followed for 20 years about 40 deaths would be avoided, while 100 GI bleeds and 17 haemorrhagic strokes would be incurred. Relative benefits ranged from a 6% reduction in relative risk (RR) for all-cause mortality (RR 0.94 [95% CI 0.88, 1.00]) to a 10% reduction in major cardiovascular events (0.90 [0.85, 0.96]) and a 15% reduction in total CHD (0.85 [0.69, 1.06]). Reported pooled odds ratios for total cancer mortality ranged between 0.76 (0.66, 0.88) and 0.93 (0.84, 1.03). Aspirin reduced reported colorectal cancer incidence (0.66 [0.9, 1.02]). Including studies where aspirin was given every other day raised the RR to 0.91 (0.74, 1.11). Reported cancer benefits begin to appear approximately five years from start of treatment. Increased relative risks of adverse events from aspirin use were reported as 37% for gastro-intestinal bleeding (1.37 [1.15, 1.62]), between 54% (1.54 [1.30, 1.82]) and 62% (1.62 [1.31, 2.00]) for major bleeds, and between 32% (1.32 [1.00, 1.74]) to 38% (1.32 [1.01, 1.82]) for haemorrhagic stroke. Conclusion: There is a fine balance between benefits and risks from regular aspirin use in primary prevention of CVD. Effects on cancer prevention have a long lead time and currently rely on post-hoc analyses of trials for other conditions. All absolute effects are small compared to the burden of these diseases. Results of ongoing trials may change the picture but presently we consider a decision to use aspirin for primary prevention of cardiovascular diseases and cancer at population level unjustified.